Construction of a high-density genetic map and localization of grazing-tolerant QTLs in Medicago falcata L. - Zhou, Xinyue; Li, Xiaojie; Zhang, Xiaoming; Yin, Dabao; Wang, Junjie; Zhao, Yan (Frontiers in Plant Science, 2022)
Background: Using genomic DNA from 79 F1 plants resulted from a crossing between parents with strong and weak grazing tolerance in Medicago falcata L., we generated an EcoRI restriction site associated DNA (RAD) sequencing library. After sequencing and assembly, a high-density genetic map with high quality SNP markers was constructed, with a total length of 1312.238 cM and an average density of 0.844 SNP/cM; (2) Methods:The phenotypic traits of 79 F1 families were observed and the QTLS of 6 traits were analyzed by interval mapping.; (3) Results: 63 QTLs were identified for seven traits with LOD values from 3 to 6 and the contribution rates from 15% to 30%. Among the 63 QTLs, 17 were for natural shoot height, 12 for rhizome Length, 10 for Shoot canopy diameter, 9 for Basal plant diameter, 6 for stem number, 5 for absolute shoot height and 4 for rhizome width. These QTLs were concentrated on LG2, LG4, LG5, LG7 and LG8. LG6 had only 6 QTLs. According to the results of QTL mapping, comparison of reference genomes and functional annotation, 10 candidate genes that may be related to grazing tolerance were screened. qRT-PCR analysis showed that two candidate genes (LOC11412291) and LOC11440209) may be the key genes related to grazing tolerance of M. falcata. (4) Conclusions: The identified trait-associated QTLs and candidate genes in this study will provide a solid foundation for future molecular breeding for enhanced grazing-tolerance in M. falcata.